2016
DOI: 10.1038/srep37724
|View full text |Cite
|
Sign up to set email alerts
|

Elderly suicide trends in the context of transforming China, 1987–2014

Abstract: In the context of rapid ageing, understanding the time-trend of elderly suicide (ES) could inform China’s efforts on suicide prevention. We examined time-trends in Chinese ES rates (ESRs) from 1987 to 2014, a period of profound social changes. Suicide rates by residence (rural/urban), gender, and 5-year age-group (65+) in 1987–2014 were provided by the Chinese Ministry of Health. Time-trends were analyzed with joinpoint analysis. The time-trend of national ESRs was downward (average annual percent change [AAPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 32 publications
1
43
3
1
Order By: Relevance
“…Last, our results indicated that gender was insignificantly associated with suicidal ideation in the current sample, which was inconsistent with previous studies claiming that the Chinese female group experience a greater risk of suicide than the male group [69,70]. However, a recent study has demonstrated a downward trend of national male-female differences in elderly suicide rates in China [71]. One possible reason lies in the marked magnitude of differences between urban and rural areas [72].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Last, our results indicated that gender was insignificantly associated with suicidal ideation in the current sample, which was inconsistent with previous studies claiming that the Chinese female group experience a greater risk of suicide than the male group [69,70]. However, a recent study has demonstrated a downward trend of national male-female differences in elderly suicide rates in China [71]. One possible reason lies in the marked magnitude of differences between urban and rural areas [72].…”
Section: Discussioncontrasting
confidence: 99%
“…The differences between male-female suicide rates in rural areas have been decreasing. Thus, the national male-female differences reduced, whereas the urban male-female differences increased [71]. However, further examinations are needed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is now the country with the largest number of older adults (OA) aged 65 years or over in the world (143.86 million in 2015) and, by 2050, this OA population will grow to 336 million, accounting for nearly one-third of the total Chinese population. [1][2][3] The rapidly increasing ageing population has posed significant challenges to health care and social services for the elderly in China where infrastructure is still underdeveloped, in particular rural areas, to manage the growing needs of this population. 4 Furthermore, the profound socioeconomic-cultural changes that have occurred in China during the past three decades pose challenges for the mental health of Chinese OA.…”
Section: Introductionmentioning
confidence: 99%
“…China is ageing much faster than almost any other country in the world in recent history, and, until now, it has been the nation with the largest number of older adult population. In 2017, the total number of Chinese older adults (65+) had reached 158.31 million, over one-tenth of China's total population, and by 2050, this number will reach 336 million, nearly one-third of the total population (National Bureau of Statistics of China 2018; Zhong et al 2016a). However, the infrastructure of China has not been prepared to meet older adults' growing needs for healthcare and social services.…”
Section: Introductionmentioning
confidence: 99%